Phraseological Units in English: Classification, Idiomaticity, and Translation Challenges - Pulatova Khilola G`ayrat qizi (Journal of Innovation in Education and Social Research, 2025)
Phraseological units, commonly known as idioms and fixed expressions, form a vital component of the English language, enriching communication with cultural and semantic depth. This article explores their classification based on structural and semantic criteria, delves into the concept of idiomaticity as a measure of non-literal meaning, and examines the inherent challenges in translating these units across languages. Drawing on linguistic theories and practical examples, the discussion highlights how fixedness and opacity complicate translation processes, often requiring creative strategies to preserve meaning, cultural nuances, and stylistic effects. The analysis underscores the importance of understanding phraseology for effective cross-cultural communication and language learning.